REKONSTRUKSI FILSAFAT ILMU DALAM PENDIDIKAN ‎AGAMA ISLAM: PERSPEKTIF ONTOLOGI, EPISTEMOLOGI, ‎DAN AKSIOLOGI - Ahmad Fadly; Muhammad Zalnur; Efendi (PT. Sulthan Journal Publisher, 2025)
Islamic Religious Education (IRE) plays a strategic role in shaping the character, morality, and social awareness of students. However, in practice, IRE often faces fundamental problems in the form of normative-dogmatic tendencies, the dominance of a textual approach, and a weak transformative orientation. These problems indicate that the crisis in PAI is not only pedagogical in nature, but is rooted in the weak foundation of its scientific philosophy. This article aims to reconstruct the philosophy of science in Islamic Religious Education through an integrative ontological, epistemological, and axiological perspective. This study uses the library research method with a descriptive-analytical and critical approach to the literature on the philosophy of science and Islamic education, both classical and contemporary. The results of the study show that the ontology of PAI is still reduced to the transfer of religious doctrine, its epistemology is dominated by a textual approach that lacks dialogue, and its axiology tends to stop at cognitive-ritual goals. The discussion leads to a proposal for the reconstruction of the philosophy of Islamic Religious Education (IRE) that positions education as a process of shaping the existence of faithful and civilized human beings, building an integrative epistemology between revelation, reason, and experience, and directing science towards the internalization of values, ethics, and social responsibility. This article asserts that the integration of ontology, epistemology, and axiology is an important foundation for the development of critical, humanistic, and transformative Islamic Religious Education, as well as relevant to the challenges of contemporary civilization.